2004
DOI: 10.1159/000076952
|View full text |Cite
|
Sign up to set email alerts
|

Burn Septicaemia in Kuwait: Associated Demographic and Clinical Factors

Abstract: Objective: To study the demographic and clinical factors associated with burn septicaemia patients in Kuwait. Materials and Methods: All burn in-patients, who developed septicaemia at the Burns Unit, Al-Babtain Centre for Burns and Plastic Surgery, Kuwait, during a 9-year period (June 1992 to May 2001) were included in the study. The data were recorded for age, sex, nationality, cause and percentage of burns, inhalation injury, resuscitation, number of episodes, septicaemia on post-burn day, the microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…reported that patients with ≥20% total body surface area burns show a higher risk of bacteremia [31], and Bang et al . found that the patients with extensive flame burns are prone to septicemia [32]. In our study,patients with KP-BSIs, with the infection source from skin and soft tissue, were accepted to the burn center of the hospital, and all suffered from flame injuries.…”
Section: Discussionmentioning
confidence: 99%
“…reported that patients with ≥20% total body surface area burns show a higher risk of bacteremia [31], and Bang et al . found that the patients with extensive flame burns are prone to septicemia [32]. In our study,patients with KP-BSIs, with the infection source from skin and soft tissue, were accepted to the burn center of the hospital, and all suffered from flame injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Polymicrobial BSI frequently occurs in adult and pediatric patients with serious underlying conditions. 12 " 16 ' 22,23 In adults, these conditions include cancer, 12 hospitalization in the intensive care unit, 13 chronic hemodialysis, 14 burns, 15 and acquired immune deficiency syndrome. 16 Reports of BSI in pediatric patients are less common, but associated underlying conditions are similar to those described in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 included studies, 13 were crosssectional studies and eight were cohort studies. These studies involved at least 8455 patients, primarily located in India (four studies), 2,[6][7][8] the USA (three studies), [9][10][11] China (two studies), 12,13 Iraq (two studies), 14,15 Kuwait (two studies), 16,17 and Sweden (two studies). 18,19 The other study populations were located in Ghana, 20 Iran, 21 Israel, 22 Lithuania, 23 Pakistan, 24 and Korea.…”
Section: Study Characteristicsmentioning
confidence: 99%